The Mediating Role of Brand Image in Celebrity Endorser and E-WOM Effects on Gen Z's MS GLOW Purchase Decisions in Semarang - Syafaq, Shandya Aissy; Firdaus, Firdaus; Abdullah, Zailani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study examines the mediating role of Brand Image in the relationship between Celebrity Endorsers, Electronic Word of Mouth (E-WOM), and purchasing decisions among Generation Z consumers of MS GLOW skincare products in Semarang, Indonesia. Employing a quantitative approach with twenty measurement indicators across four constructs and using an accidental sampling technique, the study investigates how different communication sources influence Gen Z consumers’ perceptions and purchase behavior in the local skincare market. The findings reveal that Celebrity Endorsers neither significantly shape Brand Image nor directly influence purchasing decisions, indicating that celebrity-based persuasion has limited effectiveness for this consumer segment. In contrast, E-WOM exerts a positive and significant effect on both Brand Image and purchasing decisions, underscoring the importance of peer-generated information in building trust and guiding consumer choice. Brand Image is also found to significantly influence purchasing decisions and partially mediate the relationship between E-WOM and purchase behavior, while no mediating effect is observed in the relationship between Celebrity Endorsers and purchasing decisions. These results empirically demonstrate that, within the context of Gen Z skincare consumption in Semarang, peer communication plays a more decisive role than celebrity endorsement. Theoretically, this study refines branding and consumer behavior literature by clarifying the differentiated influence pathways of E-WOM and endorsement cues. Practically, the findings suggest that skincare brands targeting Gen Z should prioritize peer-based digital engagement strategies over celebrity-driven promotion.